Optimization of Barrier Pillar Design in Longwall Mining with Top Coal Caving in Spontaneous Combustion Coal Seam - Qiang Fu; Ke Yang; Qinjie Liu; Shuai Liu; Xiang He; Xin Lyu (Geofluids)
Determining a reasonable barrier pillar along gob-side entry of spontaneous combustion coal seam is of great significance to the prevention of spontaneous combustion. In this paper, considering the actual situation of 4301 and 4302 working faces of II-class spontaneous combustion coal seam in Changheng Mine, the characteristics of rock mass collapse and mining-induced stress redistribution of barrier pillar and adjacent area were analyzed, the cusp catastrophe model of coal pillar instability and the theoretical model of limit width of coal pillar air leakage spontaneous combustion were established, and a measurement scheme of side abutment pressure in 4301 working face was carried out. The theoretical model of the coal pillar along the gob-side entry shows that its instability is related to density of overlying strata, physical and mechanical parameters of coal body, dip angle of coal seam and weak face, and buried depth and mining width of working face. And the coal pillar in 4302 working face will be unstable if the width a≤6.8 m. Field measured data shows that 2-8 m is the stress-relaxation area of side solid coal. Then, the width of coal pillar was determined as 7 m. The maximum displacement of rib-to-rib and roof-to-floor of 4302 tailentry was 520 mm and 280 mm, respectively. The coal spontaneous combustion (CSC) observation monitoring results showed that the carbon monoxide volume fraction was in the normal range during the entire process of mining, and no other signs of gas were found. The research results can provide a reference for the barrier pillar designing in the mines under similar conditions.